IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS GAMES EDUCAPLAY UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA SD - Lisa Agustin; Tasi’awati Salsa Kaliwanovia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the low learning interest and motivation of students caused by conventional teaching methods and limited use of interactive learning media. One innovative alternative is the use of digital game-based learning media such as Educaplay. This study aims to determine the implementation of game-based learning media Educaplay in improving learning interest and motivation of third-grade students at SD Islam Al Hikmah in Civic Education on the topic of rights and obligations. This research employed a descriptive qualitative approach with a case study design. The research subjects consisted of 16 third-grade students and a classroom teacher. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity ensured through triangulation techniques. The results indicate that the implementation of Educaplay creates a more interactive and participatory learning environment. Students showed increased enthusiasm, focus, and active involvement during the learning process. In addition, students’ learning interest and motivation improved, as reflected in stronger intrinsic interest, higher enthusiasm, active participation, and positive responses to learning activities. Therefore, game-based learning media Educaplay is effective in enhancing learning interest and motivation of elementary school students.